Cushioning Film

A porous metal sheet-based buffer film addresses the vulnerabilities of OLEDs by providing shock resistance, electromagnetic shielding, and heat dissipation, ensuring effective performance and durability.

JP7625325B2Active Publication Date: 2025-02-03LG CHEM LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023514477
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-30
Filing Date
2021-09-02
Publication Date
2025-02-03
Estimated Expiration
2041-09-02

AI Technical Summary

Technical Problem

Organic light-emitting devices (OLEDs) are vulnerable to external impacts, electromagnetic interference, and heat generation, which are exacerbated in mobile devices, and existing cushioning members do not adequately address these issues.

Method used

A buffer film comprising a porous metal sheet with specific metal compositions and structures is used to provide shock resistance, electromagnetic wave shielding, and heat dissipation, ensuring low reflectance to maintain device visibility.

Benefits of technology

The buffer film effectively absorbs shocks, dissipates heat, and shields electromagnetic waves, enhancing the performance and durability of OLEDs while maintaining optical clarity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007625325000002
    Figure 0007625325000002
  • Figure 0007625325000003
    Figure 0007625325000003
  • Figure 0007625325000004
    Figure 0007625325000004
Patent Text Reader

Abstract

In this application, a buffer film including a porous metal sheet having an average reflectance of 50% or less for light in the wavelength range of 400 to 800 nm can exhibit the heat dissipation, electromagnetic wave shielding, and impact resistance (or impact mitigation) required for OLEDs by itself, and can ensure the properties required for OLEDs without increasing the cost, complicating the process, or increasing the thickness of the OLED, and an OLED including the buffer film can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority based on Korean Patent Application No. 10-2020-0111885 filed on September 2, 2020, Korean Patent Application No. 10-2020-0116206 filed on September 10, 2020, and Korean Patent Application No. 10-2020-0143626 filed on October 30, 2020, and the contents disclosed in the documents of said Korean patent applications are incorporated by reference into this specification.

[0002] The present application relates to a buffer film and its uses. [Background technology]

[0003] Since an organic light emitting device emits light by itself, it is advantageous for realizing a thinner device than other devices such as a liquid crystal device (LCD), and is also advantageous for forming a flexible device such as a foldable or rollable device.

[0004] However, organic light emitting devices are vulnerable to external shocks such as a drop shock, and as organic light emitting devices are increasingly used in mobile devices, the problems caused by the external shocks become more serious.

[0005] As devices incorporating an organic light emitting device are made thinner, problems with electromagnetic waves and heat generated by the organic light emitting device or electronic elements connected thereto become more serious.

[0006] The organic light-emitting device includes a substrate on which an organic light-emitting layer is formed, and may include a driving circuit unit for driving the organic light-emitting layer and an electronic element for transmitting a signal to the driving circuit unit. When an electronic element is present, the electronic element may be located on the rear surface of the substrate. As illustrated in FIG. 1, in the above case, the organic light-emitting device may have a structure in which an organic light-emitting layer 20 is present on a first surface of a substrate 10 and an electronic element 30 is present on a second surface of the substrate.

[0007] In the above-mentioned structure, problems may occur when heat generated in the organic light emitting layer or the driving circuit is transferred to the electronic device, or conversely, heat generated in the electronic device or the battery is transferred to the organic light emitting layer or the driving circuit, and therefore it is necessary to efficiently dispose of the heat generated as described above.

[0008] Furthermore, when electromagnetic waves generated by electronic elements are transmitted to organic light-emitting layers, the performance may be degraded, and the electromagnetic waves may also have a detrimental effect on the user of the device.

[0009] Patent Document 1 discloses a structure for dealing with the problem of external impacts by arranging a cushioning member made of urethane or the like under the substrate of an organic light-emitting device.

[0010] However, the structure disclosed in Patent Document 1 is insufficient to ensure sufficient impact resistance when applied to mobile devices and the like.

[0011] Furthermore, the structure disclosed in Patent Document 1 does not take into consideration the problems of electromagnetic waves and heat generated by the device.

[0012] In order to solve the electromagnetic wave and heat generation problems, it may be possible to consider adding a component that can further block electromagnetic waves or a component that can solve the heat generation problem to the device, but the introduction of such a component makes it difficult to configure the device thin. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Korean Patent Registration Publication No. 10-0965251 Summary of the Invention [Problem to be solved by the invention]

[0014] The present application aims to provide a buffer film and uses thereof, in particular a buffer film for an organic light-emitting device and uses thereof. [Means for solving the problem]

[0015] Among the physical properties described in this specification, those whose results are affected by the measurement temperature are the results measured at room temperature, unless otherwise specified.

[0016] The term "room temperature" refers to a natural temperature that is neither heated nor cooled, and means, for example, any one temperature within the range of 10° C. to 30° C., such as a temperature of about 23° C. or about 25° C. In addition, the unit of temperature in this specification is Celsius (° C.) unless otherwise specified.

[0017] Of the physical properties described in this specification, those whose results are affected by the measurement pressure are the results measured at normal pressure, unless otherwise specified.

[0018] The term "normal pressure" refers to the natural pressure that is not adjusted by methods such as pressurization or depressurization, and is usually at atmospheric pressure level, which may be about 900 hPa to 1,200 hPa.

[0019] In the present specification, in the case of a physical property whose result is affected by the measurement humidity, the physical property is a physical property measured at the natural humidity without any special adjustment at room temperature and pressure.

[0020] The present application provides a buffer film. The buffer film of the present application can be applied to various applications that require impact mitigation. In one example, the buffer film can be effectively used for an organic light emitting device (hereinafter referred to as OLED).

[0021] The buffer film of the present application includes a porous metal sheet. The term "porous metal sheet" means a metal sheet having one or more voids formed inside or on a surface thereof, and the metal sheet has a shape generally called a film, sheet or layer.

[0022] The porous metal sheet contains a metal as a main component. Therefore, the weight ratio of the metal based on the total weight of the porous metal sheet may be about 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more. Since the porous metal sheet may contain only metal, the upper limit of the weight ratio of the metal is 100% by weight. The above category of metal also includes so-called metal alloys. Also, the metal may be contained in the porous metal sheet in the form of an oxide, nitride, or oxynitride.

[0023] The porous metal sheet can exhibit an effect of buffering external impacts due to a structure including voids. In addition, the heat dissipation effect can be secured by securing the heat conduction characteristics required by the device through the selection of the metal material applied to the porous metal sheet. In addition, the voids contained in the porous metal sheet can also exhibit the effect of eliminating or blocking electromagnetic waves. As a result, the buffer film of the present application can exhibit the heat dissipation properties, electromagnetic wave shielding properties, impact resistance and impact mitigation properties required by the device with only the porous metal sheet. Therefore, the buffer film of the present application can solve various problems occurring in OLEDs and the like without increasing the price, complicating the process and increasing the thickness.

[0024] The porous metal sheet included in the buffer film of the present application may exhibit an average reflectance of 50% or less for light in the wavelength range of 400 to 800 nm. In other examples, the average reflectance may be 49% or less, 47% or less, 45% or less, 43% or less, 41% or less, 39% or less, 37% or less, 35% or less, 33% or less, 31% or less, or 29% or less. Such a low reflectance is particularly necessary when the buffer film is applied to an OLED. An OLED usually includes a reflective electrode or a reflector for light emission, and such a reflective electrode or reflector reduces the visibility of the device, so various approaches have been taken to solve this problem. When a metal material is applied to the buffer film, the above problem may be highlighted due to the inherent reflective properties of the metal. In the present application, by adjusting the reflectance of the porous metal sheet as described above, the buffer film can exhibit the desired performance without reducing the optical properties of the OLED or the like.

[0025] The lower the average reflectance of the porous metal sheet, the more advantageous it is for light in the wavelength range of 400 to 800 nm, so the lower limit is not particularly limited. Considering the reflection characteristics of general metal materials, the average reflectance may be, for example, about 10% or more, 15% or more, or 25% or more.

[0026] The average reflectance is obtained by measuring the reflectance for each wavelength starting from 400 nm to 800 nm at intervals of 0.5 nm, and averaging the measured values. Specifically, the average reflectance is a value measured by the method presented in the examples.

[0027] The method for adjusting the reflectance of the porous metal sheet is not particularly limited. The inherent reflectance characteristics of metal materials are known for each metal, and the reflectance can be achieved by selecting an appropriate metal in consideration of such reflectance characteristics. If necessary, two or more metals can be used to adjust the reflectance, as described below.

[0028] The porous metal sheet also has a resistivity of 1.0×10-5 Ωcm or more. The buffer film of the present application may be included in electronic / electrical devices such as OLEDs to ensure buffering, heat dissipation, and / or electromagnetic wave shielding. Here, when the resistivity of the porous metal sheet is adjusted to the above range, a suitable insulating part or conductive part can be formed in the device through the porous metal sheet. Therefore, by adjusting the resistivity of the porous metal sheet as described above, the structure of the device to which the buffer film of the present application is applied can be controlled more simply and efficiently. The method of measuring the resistivity is described in the following examples. There is no particular limitation on the method of forming the porous metal sheet so that the resistivity can be achieved. Since the inherent resistivity of metal materials is known, an appropriate metal can be selected so that a porous metal sheet having a resistivity in the above range can be formed. In order to provide the porous metal sheet with heat dissipation, it is advantageous to select a metal with as good thermal conductivity as possible, but generally, metals with good thermal conductivity often exhibit low resistivity. Therefore, in order to simultaneously secure excellent thermal conductivity and a specific resistance in the above range, it is advantageous to form the porous metal sheet using two or more metals. In another example, the specific resistance is 1.1×10 -5 Ωcm or more, 1.2×10 -5 Ωcm or more, 1.3×10 -5 Ωcm or more, 1.4×10 -5 Ωcm or more, 1.5×10 -5 Ωcm or more, 1.6×10 -5 Ωcm or more, 1.7×10 -5 Ωcm or more, 1.8×10 -5 Ωcm or more, 1.9×10 -5 Ωcm or more, 2.0×10 -5 Ωcm or more, 2.1×10 -5 Ωcm or more or 2.2×10 -5 Ωcm or more or 9×10 -5 Ωcm or less, 8×10 -5 Ωcm or less, 7×10 -5 Ωcm or less, 6×10 -5 Ωcm or less, 5×10 -5 Ωcm or less, 4×10 -5 Ωcm or less, 3×10-5 Ωcm or less, 2×10 -5 Ωcm or less, 1.5×10 -5 It may be about Ωcm or less.

[0029] The porous metal sheet is 25 mm 2 The thermal diffusivity may be 30 mm / s or more. The thermal diffusivity is a value measured by the method described in the examples of the present specification. When the porous metal sheet has a thermal diffusivity in the above range, the buffer film of the present application may exhibit heat dissipation properties in devices such as OLEDs. In another example, the thermal diffusivity is 30 mm / s or more. 2 / s or more, 35mm 2 / s or more, 40mm 2 / s or more, 45mm 2 / s or more, 50mm 2 / s or more, 55mm 2 / s or more, 60mm 2 / s or more, 65mm 2 / s or more, 70mm 2 / s or more, 75mm 2 / s or more, 80mm 2 / s or more, 85mm 2 / s or more, 90mm 2 / s or more, 95mm 2 / s or more, 100mm 2 / s or more, 105mm 2 / s or more, 110mm 2 / s or more, 115mm 2 / s or more, 120mm 2 / s or more, 125mm 2 / s or more, 130mm 2 / s or more, 135mm 2 / s or more, 140mm 2 / s or more, 145mm 2 / s or more, 150mm 2 / s or more, 155mm 2 / s or more, 160mm 2 / s or more, 165mm 2 / s or more, 170mm 2 / s or more, 175mm 2 / s or more, 180mm 2 / s or more, 185mm 2 / s or more, 190mm 2 / s or more, 195mm 2 / s or more, 200mm 2 / s or more, 205mm 2 / s or more, 210mm 2 / s or more, 215mm 2 / s or more, 220mm 2 / s or more, 225mm 2 / s or more, 230mm 2 / s or more, 235mm 2 / s or more, 240mm 2 / s or more, 245mm 2 / s or more, 250mm 2 / s or more, 255mm 2 / s or more, 260mm 2 / s or more, 265mm 2 / s or more, 270mm 2 / s or more, 275mm 2 / s or more, 280mm 2 / s or more, 285mm 2 / s or more, 290mm 2 / s or more or 295mm 2 / s or more, or 300 mm 2 / s or less, 295mm 2 / s or less, 290mm 2 / s or less, 285mm 2 / s or less, 280mm 2 / s or less, 275mm 2 / s or less, 270mm 2 / s or less, 265mm 2 / s or less, 260mm 2 / s or less, 255mm 2 / s or less, 250mm 2 / s or less, 245mm 2 / s or less, 240mm 2 / s or less, 235mm 2 / s or less, 230mm 2 / s or less, 225mm 2 / s or less, 220mm 2 / s or less, 215mm 2 / s or less, 210mm 2 / s or less, 205mm 2 / s or less, 200mm 2 / s or less, 195mm 2 / s or less, 190mm 2 / s or less, 185mm 2 / s or less, 180mm 2 / s or less, 175mm 2 / s or less, 170mm 2 / s or less, 165mm 2 / s or less, 160mm 2 / s or less, 155mm 2 / s or less, 150mm 2 / s or less, 145mm 2 / s or less, 140mm 2 / s or less, 135mm 2 / s or less, 130mm 2 / s or less, 125mm 2 / s or less, 120mm 2 / s or less, 115mm 2 / s or less, 110mm 2 / s or less, 105mm 2 / s or less, 100mm 2 / s or less, 95mm 2 / s or less, 90mm 2 / s or less, 85mm 2 / s or less, 80mm 2 / s or less, 75mm 2 / s or less, 70mm 2 / s or less, 65mm 2 / s or less, 60mm 2 / s or less, 55mm 2 / s or less, 50mm 2 / s or less, 45mm 2 / s or less or 40mm 2 / s or less.

[0030] The above thermal diffusivity can be achieved by forming the porous metal sheet using an appropriate metal material in consideration of the thermal conductivity characteristics of each metal material. In order to simultaneously achieve the above-mentioned reflectance, thermal conductivity, and resistivity, the porous metal sheet can be formed using two or more metals, as described below.

[0031] The porous metal sheet included in the buffer film has the form of a film, sheet or layer as described above. The porous metal sheet in this form may have a first main surface and a second main surface facing the first main surface. The first and second main surfaces are two surfaces having a large relative area to other surfaces among the surfaces identified in the porous metal sheet in the form of the film, sheet or layer, and the first and second main surfaces are usually opposed to each other.

[0032] The first and second main surfaces may have different surface roughnesses. By making the surface roughnesses of the first and second main surfaces of the porous metal sheet different, the buffering properties and durability of the device can be further improved. For example, when the buffer film of the present application is applied to an OLED, as described below, the buffer film can be applied to a surface of a substrate on which an organic light-emitting layer is formed, opposite to the surface on which the organic light-emitting layer is formed. Here, when the buffer film is arranged such that the surface having a larger surface roughness among the first and second main surfaces of the porous metal sheet (hereinafter, it is assumed that the first main surface has a larger surface roughness) faces the organic light-emitting layer, a more excellent impact buffering effect can be obtained. Without being limited by theory, the reason why such an effect can be obtained is presumed to be as follows. Generally, the impact that must be buffered among the impacts applied to an OLED is the impact applied in the organic light-emitting layer in the direction of the substrate. Therefore, when the buffer film is disposed such that the first of the first and second main surfaces faces the organic light-emitting layer, an impact is applied to the first of the first and second main surfaces first, and the applied impact is transmitted from the first to the second main surface. Here, if the surface roughness of the first main surface to which the impact is applied first is large, the impact can be absorbed more efficiently than when the surface roughness is small. In addition, the applied impact is dispersed after being transmitted to the second main surface, and if the second main surface to which the impact is dispersed exhibits a relatively small surface roughness, the impact can be dispersed more effectively.

[0033] In order to dispose the buffer film as described above, an attachment layer (described later) is attached to the porous metal sheet as necessary, but in order to dispose the buffer film as described above, the attachment layer must be formed on the first main surface, which has a larger surface roughness. Here, since the first main surface has a large surface roughness, it can exhibit better adhesion to the attachment layer due to the so-called anchoring effect, etc., and as a result, the durability of the device can be improved.

[0034] The degree of difference in surface roughness between the first and second main surfaces is not particularly limited, but in order to properly ensure the above effect, it can be adjusted so that the ratio 1Sa / 2Sa of the surface roughness 1Sa of the first main surface to the surface roughness 2Sa of the second main surface exceeds 1 and is 3 or less. In other examples, the ratio 1Sa / 2Sa may be 1.05 or more, 1.1 or more, 1.15 or more, 1.2 or more, 1.25 or more, 1.3 or more, 1.35 or more, 1.4 or more, 1.45 or more, 1.5 or more, 1.55 or more, 1.6 or more, 1.65 or more, or 1.7 or more, or 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, or 1.2 or less.

[0035] Under the above-mentioned ratio, the surface roughness 1Sa of the first main surface may be 6.5 μm or more. In other examples, the surface roughness 1Sa may be about 6.7 μm or more, 6.9 μm or more, 7.1 μm or more, 7.3 μm or more, 7.5 μm or more, 7.7 μm or more, 7.9 μm or more, 8.1 μm or more, 8.3 μm or more, 8.5 μm or more, or 8.7 μm or more, or about 20 μm or less, 18 μm or less, 16 μm or less, 14 μm or less, 12 μm or less, 10 μm or less, or 8 μm or less.

[0036] The method for measuring the surface roughness for the first and second main surfaces is described in the Examples section.

[0037] The method of controlling the surface roughness of both surfaces of the porous metal sheet as described above is not particularly limited. As described later, in the present application, the porous metal sheet may be a metal foam, a sintered metal fiber sheet, or a metal mesh. The metal foam may be manufactured by preparing a precursor using a slurry containing a metal powder and sintering the precursor. For example, the surface roughness may be controlled by adjusting the particle size of the metal powder in the slurry in the above process. The surface roughness of the sintered metal fiber sheet may also be controlled by controlling the wire diameter of the applied metal fiber, and in the case of the metal mesh, the surface roughness may be controlled by controlling the mesh size. There is also no particular limit to the method of making the surface roughness of the first and second main surfaces different. In the process of manufacturing the metal foam or sintered metal fiber sheet among the porous metal sheets, a sintering process may be performed on the precursor. Here, the precursor may also be in the form of a film, sheet or layer, and in the course of the sintering process, one main surface of the film, sheet or layer may be sintered in a state where it is in contact with a relatively smooth surface and the opposite surface is exposed to air, or the opposite surface may be sintered in a state where it is in contact with a rough surface, thereby producing a porous metal sheet having different surface roughness on both main surfaces. In addition, if the above method is not used or is used, when it is necessary to adjust the surface roughness of the main surface of the produced porous metal sheet, the surface roughness of the porous metal sheet may be adjusted by applying a method such as pressing the surface of the porous metal sheet.

[0038] The porous metal sheet of the buffer film of the present application may have an electromagnetic wave shielding ability. Among metals, metals having electrical conductivity may exhibit reflective properties with respect to electromagnetic waves. Therefore, electromagnetic waves propagated to the buffer film may be reflected and shielded by the porous metal sheet. In addition, since the porous metal sheet includes voids inside or on the surface, electromagnetic waves propagated to the porous metal sheet may be repeatedly reflected within the voids, and in the process, the electromagnetic waves may be lost due to interference, etc.

[0039] In one example, the porous metal sheet may have an electromagnetic wave shielding property of 70 dB or more at 30 MHz to 1.5 GHz. In other examples, the electromagnetic wave shielding property may be 75 dB or more, 80 dB or more, 85 dB or more, 86 dB or more, 87 dB or more, 88 dB or more, 89 dB or more, 90 dB or more, 91 dB or more, 92 dB or more, 93 dB or more, 94 dB or more, or 95 dB or more. The upper limit of the electromagnetic wave shielding property is not particularly limited, but may be, for example, about 200 dB or less, 190 dB or less, 180 dB or less, 170 dB or less, 160 dB or less, 150 dB or less, 140 dB or less, 130 dB or less, 120 dB or less, 100 dB or less, or about 100 dB or less. Such electromagnetic wave shielding properties can be achieved by controlling the pore characteristics, thickness and material of the porous metal sheet as follows: The electromagnetic wave shielding properties can be measured according to ASTM D4935 or ASTM ES7 standards.

[0040] The thickness of the porous metal sheet can be controlled to ensure the required impact resistance and to realize the above-mentioned electromagnetic wave shielding ability and heat dissipation characteristics, etc. For example, the thickness of the porous metal sheet may be about 50 μm or more, 65 μm or more, 70 μm or more, 75 μm or more, 80 μm or more, 85 μm or more, 90 μm or more, 95 μm or more, 100 μm or more, 105 μm or more, 110 μm or more, 115 μm or more, 120 μm or more, 125 μm or more, 130 μm or more, 135 μm or more, 140 μm or more, 145 μm or more, 150 μm or more, 155 μm or more, 160 μm or more, 165 μm or more, 170 μm or more, 175 μm or more, 180 μm or more, 185 μm or more, 190 μm or more, 195 μm or more, or 200 μm or more. The thicker the porous metal sheet, the more advantageous it is in securing the heat dissipation properties, electromagnetic shielding properties, and impact resistance required for OLEDs, etc., so the upper limit of the thickness is not particularly limited. However, if the porous metal sheet is too thick, it is disadvantageous in realizing a thin device, so the thickness of the porous metal sheet may be controlled within a range of about 1000 μm or less, 900 μm or less, 800 μm or less, 700 μm or less, 600 μm or less, 500 μm or less, 400 μm or less, 300 μm or less, 200 μm or less, or 150 μm or less.

[0041] The porous metal sheet may be made of various known metals or metal alloys. By selecting an appropriate material in consideration of the reflectance, thermal conductivity, and electrical conductivity of the metal material, a porous metal sheet exhibiting the above-mentioned characteristics can be obtained.

[0042] For example, the porous metal sheet may include or be composed of any one metal selected from the group consisting of stainless steel, copper, gold, platinum, silver, aluminum, nickel, manganese, iron, cobalt, magnesium, molybdenum, tungsten, and zinc, or two or more of the above, but is not limited thereto.

[0043] In the porous metal sheet, the content of any one metal selected from the group consisting of stainless steel, copper, gold, platinum, silver, aluminum, nickel, manganese, iron, cobalt, magnesium, molybdenum, tungsten, and zinc, or two or more of the above, may be about 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more based on the total weight of the porous metal sheet. Since the porous metal sheet may contain only the metal, the upper limit of the weight ratio of the metal is 100% by weight.

[0044] In one example, the porous metal sheet may include a first metal and a second metal different from the first metal.

[0045] In one example, the first and second metals may have Young's modulus in different ranges.

[0046] For example, the first metal may have a Young's modulus of 160 GPa or less, and the second metal may have a Young's modulus of more than 160 GPa. The Young's modulus of the metals is a value determined according to ASTM E111.

[0047] In other examples, the Young's modulus of the first metal may be approximately 155 GPa or less, 150 GPa or less, 145 GPa or less, 140 GPa or less, 135 GPa or less, 130 GPa or less, 125 GPa or less, 120 GPa or less, or 115 GPa or less, or approximately 50 GPa or more, 55 GPa or more, 60 GPa or more, 65 GPa or more, 70 GPa or more, 75 GPa or more, 80 GPa or more, 85 GPa or more, 90 GPa or more, 95 GPa or more, 100 GPa or more, 105 GPa or more, 110 GPa or more, 115 GPa or more, 120 GPa or more, or 125 GPa or more.

[0048] In other examples, the Young's modulus of the second metal is about 165 GPa or more, 170 GPa or more, 175 GPa or more, 180 GPa or more, 185 GPa or more, 190 GPa or more, 195 GPa or more, or 200 GPa or more, or 400 GPa or less, 395 GPa or less, 390 GPa or less, 385 GPa or less, 380 GPa or less, 375 GPa or less, 370 GPa or less, 365 GPa or less, 360 GPa or less, 355 GPa or less, 350 GPa or less, 345 GPa or less, 340 GPa or less, 335 GPa or less, or 330 GPa or less. , 325 GPa or less, 320 GPa or less, 315 GPa or less, 310 GPa or less, 305 GPa or less, 300 GPa or less, 295 GPa or less, 290 GPa or less, 285 GPa or less, 280 GPa or less, 275 GPa or less, 270 GPa or less, 265 GPa or less, 260 GPa or less, 255 GPa or less, 250 GPa or less, 245 GPa or less, 240 GPa or less, 235 GPa or less, 230 GPa or less, 225 GPa or less, 220 GPa or less, 215 GPa or less, 210 GPa or less, or 205 GPa or less.

[0049] By using the first and second metals each having the above-mentioned Young's modulus, it is possible to obtain a porous metal sheet that efficiently ensures the desired shock mitigation properties.

[0050] In one example, the first and second metals may have resistivities in different ranges.

[0051] For example, the first metal has a resistivity of 4.3×10 -6 The second metal has a resistivity of 4.3×10 -6 The resistivity of the metal may be greater than Ωcm as determined by ASTM E1004-17.

[0052] In another example, the resistivity of the first metal is 4.1×10 -6 Ωcm or less, 3.9×10 -6 Ωcm or less, 3.7×10 -6 Ωcm or less, 3.5×10 -6Ωcm or less, 3.3×10 -6 Ωcm or less, 3.1×10 -6 Ωcm or less, 2.9×10 -6 Ωcm or less, 2.7×10 -6 Ωcm or less, 2.5×10 -6 Ωcm or less, 2.3×10 -6 Ωcm or less, 2.1×10 -6 Ωcm or less, 1.9×10 -6 Ωcm or less or 1.7×10 -6 Ωcm or less, or 0.5×10 -6 Ωcm or more, 0.7×10 -6 Ωcm or more, 0.9×10 -6 Ωcm or more, 1.0×10 -6 Ωcm or more, 1.1×10 -6 Ωcm or more, 1.3×10 -6 Ωcm or more, 1.5×10 -6 Ωcm or more or 1.7×10 -6 It may be about Ωcm or more.

[0053] In another example, the resistivity of the second metal is 4.5×10 -6 Ωcm or more, 4.9×10 -6 Ωcm or more, 5.1×10 -6 Ωcm or more, 5.3×10 -6 Ωcm or more, 5.5×10 -6 Ωcm or more, 5.7×10 -6 Ωcm or more, 5.9×10 -6 Ωcm or more, 6.1×10 -6 Ωcm or more, 6.3×10 -6 Ωcm or more, 6.5×10 -6 Ωcm or more, 6.7×10 -6 Ωcm or more or 6.9×10 -6 Ωcm or more, or 15×10 -6 Ωcm or less, 14×10 -6 Ωcm or less, 13×10 -6 Ωcm or less, 12×10 -6 Ωcm or less, 11×10 -6 Ωcm or less, 10×10 -6 Ωcm or less, 9.9×10 -6 Ωcm or less, 9.7×10-6 Ωcm or less, 9.5×10 -6 Ωcm or less, 9.3×10 -6 Ωcm or less, 9.1×10 -6 Ωcm or less, 8.9×10 -6 Ωcm or less, 8.7×10 -6 Ωcm or less, 8.5×10 -6 Ωcm or less, 8.3×10 -6 Ωcm or less, 8.1×10 -6 Ωcm or less, 7.9×10 -6 Ωcm or less, 7.7×10 -6 Ωcm or less, 7.5×10 -6 Ωcm or less, 7.3×10 -6 Ωcm or less, 7.1×10 -6 Ωcm or less or 6.9×10 -6 It may be about Ωcm or less.

[0054] By applying the first and second metals each having a resistivity within the above range, a porous metal sheet having the desired thermal conductivity and electrical resistance properties at the same time can be more effectively formed.

[0055] In one example, the first and second metals may have thermal conductivities in different ranges.

[0056] For example, the first metal may have a thermal conductivity of 150 W / mK or more, and the second metal may have a thermal conductivity of less than 150 W / mK. The thermal conductivities of the metals are values ​​confirmed by ASTM E1225.

[0057] In other examples, the thermal conductivity of the first metal is about 1000 W / mK or less, 950 W / mK or less, 900 W / mK or less, 850 W / mK or less, 800 W / mK or less, 750 W / mK or less, 700 W / mK or less, 650 W / mK or less, 600 W / mK or less, 550 W / mK or less, 500 W / mK or less, or 450 W / mK or less; mK or more, 220 W / mK or more, 230 W / mK or more, 240 W / mK or more, 250 W / mK or more, 260 W / mK or more, 270 W / mK or more, 280 W / mK or more, 290 W / mK or more, 300 W / mK or more, 310 W / mK or more, 320 W / mK or more, 330 W / mK or more, 340 W / mK or more, 350 W / mK or more, 360 W / mK or more, 370 W / mK or more, 380 W / mK or more, 390 W / mK or more, or about 400 W / mK or more.

[0058] In other examples, the thermal conductivity of the second metal may be approximately 10 W / mK or more, 20 W / mK or more, 30 W / mK or more, 40 W / mK or more, 50 W / mK or more, 60 W / mK or more, 70 W / mK or more, 80 W / mK or more, or 90 W / mK or more, or approximately 145 W / mK or less, 140 W / mK or less, 135 W / mK or less, 130 W / mK or less, 125 W / mK or less, 120 W / mK or less, 115 W / mK or less, 110 W / mK or less, 105 W / mK or less, 100 W / mK or less, or 95 W / mK or less.

[0059] By applying the first and second metals each having a thermal conductivity within the above range, a porous metal sheet having the desired thermal conductivity and electrical resistance properties at the same time can be more effectively formed.

[0060] The first metal may exhibit at least one characteristic selected from the group consisting of the Young's modulus, thermal conductivity, and resistivity, and in one example, may simultaneously exhibit the Young's modulus, thermal conductivity, and resistivity. The type of such metal is not particularly limited, and for example, the first metal may be copper.

[0061] The second metal may exhibit at least one characteristic selected from the group consisting of the Young's modulus, thermal conductivity, and resistivity, and in one example, may simultaneously exhibit the Young's modulus, thermal conductivity, and resistivity. The type of such metal is not particularly limited, and for example, the second metal may be copper.

[0062] In addition, the first metal may be only one type in the porous metal sheet, or two or more types of the first metal may be present in the porous metal sheet. For example, even if there are two or more metals that have Young's moduli in the above-mentioned range but are different from each other, the two or more metals are considered to be the first metal as long as the Young's moduli are within the above-mentioned range. This classification is the same for resistivity and thermal conductivity.

[0063] The second metal may be only one type in the porous metal sheet, or two or more types of second metals may be present in the porous metal sheet. For example, even if there are two or more metals that have Young's moduli in the above-mentioned range but are different from each other, the two or more metals are considered to be second metals as long as the Young's moduli are within the above-mentioned range. This classification is the same for resistivity and thermal conductivity.

[0064] The total weight ratio of the first and second metals in the porous metal sheet may be about 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, or 95% by weight or more based on the total weight of the porous metal sheet. Since the porous metal sheet may include only the first and second metals, the upper limit of the total weight ratio of the first and second metals is 100% by weight.

[0065] The first and second metals may have different thermal conductivities, resistivities, and / or Young's moduli as described above, but may have densities in a similar range. The densities of the metals are ascertained according to ASTM B923.

[0066] For example, the density of the first and second metals is 6 to 15 g / cm 3 In another embodiment, the density is in the range of 6.5 g / cm 3 More than 7g / cm 3 More than 7.5g / cm 3 More than 8g / cm 3 or more than 8.5g / cm 3 or more, or 14.5g / cm 3 Below, 14g / cm 3 Below, 13.5g / cm 3 Below, 13g / cm 3 Below, 12.5g / cm 3 Below, 12g / cm 3 Below, 11.5g / cm3 or below, 11g / cm 3 Below, 10.5g / cm 3 Less than or equal to 10g / cm 3 It may be about the same or less.

[0067] By using metals having densities in such a range, it is possible to manufacture a cushioning film that is lighter in weight while still achieving the desired effect.

[0068] The first and second metals may have different thermal conductivities, resistivities, and / or Young's moduli as described above, but may have similar Poisson's ratios as determined by ASTM E132.

[0069] For example, the Poisson's ratio of each of the first and second metals may be within a range of 0.1 to 0.7. In other examples, the Poisson's ratio may be 0.15 or more, 0.2 or more, 0.25 or more, or 0.3 or more, or about 0.65 or less, 0.6 or less, 0.55 or less, 0.5 or less, 0.45 or less, 0.4 or less, or 0.35 or less.

[0070] By using a metal having a Poisson's ratio in this range, a buffer film that exhibits the desired shock mitigation effect more efficiently can be manufactured.

[0071] The first and second metals may, independently of one another, satisfy either or both of the density and Poisson's ratios described above.

[0072] The ratio between the first and second metals in the porous metal sheet is not particularly limited. That is, since the reflectance, resistivity and thermal conductivity of the porous metal sheet depend on the content of the first and second metals, the content ratio of the first and second metals can be adjusted to satisfy the reflectance, resistivity and / or thermal conductivity.

[0073] There is no limitation on the method of simultaneously including the first and second metals in the porous metal sheet. For example, as described below, the porous metal sheet may be a metal foam, a sintered metal fiber sheet, or a metal mesh, and the first and second metals may be used simultaneously as the material of the metal foam, sintered metal fiber sheet, or metal mesh. As another method, a method may be applied in which one of the first and second metals is used to form the metal foam, sintered metal fiber sheet, or metal mesh, and then a metal layer is formed on the metal foam, sintered metal fiber sheet, or metal mesh with the other metal. The method of forming the metal layer is not particularly limited, and for example, a known method such as electrolytic plating or electroless plating may be used.

[0074] In one example, the porous metal sheet may be a so-called metal foam. As the metal foam, any known metal foam may be used without any particular limitation as long as it is made of the above-mentioned material and exhibits the above-mentioned properties (resistivity, thermal conductivity, reflectance, etc.).

[0075] Various metal foams are known in the art, and various methods for manufacturing such metal foams are also known in the art. In the present application, such known metal foams or metal foams manufactured by known methods can be applied.

[0076] The metal foam applied in the present application may be formed, for example, by a method including a step of sintering a metal foam precursor containing the above-mentioned metal. In the present application, the term "metal foam precursor" refers to a structure before a process for forming a metal foam, such as the sintering, is performed, i.e., a structure before a metal foam is generated. Although the metal foam precursor is called a porous metal foam precursor, it does not necessarily have to be porous itself, and may be called a porous metal foam precursor for convenience as long as it can finally form a metal foam, which is a porous metal structure.

[0077] The metal foam precursor may be formed using a slurry containing at least a metal component, a dispersant or solvent, and a binder, and a porous metal sheet having the desired properties may be efficiently manufactured by applying such a slurry.

[0078] The metal component may be a metal powder. Examples of the applicable metal powder are determined depending on the purpose and are not particularly limited, and may include, for example, the powder of the first and / or second metal, the powder of a metal alloy, or the powder of a mixture of metals.

[0079] The size of the metal powder is also selected in consideration of the desired porosity and surface roughness, and is not particularly limited, but for example, the average particle size of the metal powder may be in the range of about 0.1 μm to about 200 μm. In other examples, the average particle size may be about 0.5 μm or more, about 1 μm or more, about 2 μm or more, about 3 μm or more, about 4 μm or more, about 5 μm or more, about 6 μm or more, about 7 μm or more, about 8 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 25 μm or more, 30 μm or more, 35 μm or more, 40 μm or more, 45 μm or more, 50 μm or more, or 55 μm or more. In other examples, the average particle size may be about 150 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, 40 μm or less, 30 μm or less, or 20 μm or less. Metals in the metal particles may have different average particle sizes. The average particle size may be selected in an appropriate range in consideration of the shape of the desired metal foam, for example, the thickness and porosity of the metal foam. The average particle size of the metal powder described in this specification is the so-called median particle size, also called the D50 particle size. Such a median particle size is determined by a known particle size analysis method.

[0080] The ratio of the metal component (metal powder) in the slurry is not particularly limited and can be selected in consideration of the desired viscosity, process efficiency, etc. In one example, the ratio of the metal component in the slurry may be about 0.5 to 95% by weight, but is not limited thereto. In other examples, the ratio may be about 1% or more, about 1.5% or more, about 2% or more, about 2.5% or more, about 3% or more, about 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more, or about 90% or less, about 85% or less, about 80% or less, about 75% or less, about 70% or less, about 65% or less, 60% or less, 55% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, or 5% or less, but is not limited thereto.

[0081] The metal foam precursor may be formed using a slurry that includes the metal powder along with a dispersant or solvent and a binder.

[0082] As the dispersant or solvent, for example, alcohol can be used. As the alcohol, a monohydric alcohol having 1 to 20 carbon atoms such as methanol, ethanol, propanol, pentanol, octanol, 2-ethoxyethanol, 2-butoxyethanol, or terpineol, or a dihydric alcohol having 1 to 20 carbon atoms such as ethylene glycol, propylene glycol, hexanediol, octanediol, or pentanediol, or a polyhydric alcohol having 1 to 20 carbon atoms such as glycerol, texanol, or the like can be used, but the type is not limited to the above. In addition, as other solvents, appropriate solvents can be used in consideration of the solubility of the metal components and the binders described later, and solvents having a dielectric constant in the range of about 10 to 120 can also be used, but the dielectric constant may be about 20 or more, about 30 or more, about 40 or more, about 50 or more, about 60 or more, or about 70 or more, or about 110 or less, about 100 or less, or about 90 or less. Examples of such solvents include water, alcohols having 1 to 8 carbon atoms, such as ethanol, butanol, or methanol, DMSO (dimethyl sulfoxide), DMF (dimethyl formamide), or NMP (N-methylpyrrolidinone), and ester solvents such as alkyl isobutyrate (IBIBB) having an alkyl group with 1 to 20, 1 to 16, 1 to 12, 1 to 8, or 1 to 4 carbon atoms, but are not limited to these.

[0083] As the solvent or dispersant, a mixed solvent of the alcohol and the ester solvent can also be used. In this case, for example, about 1 to 100 parts by weight of the ester solvent can be used per 100 parts by weight of the alcohol. In other examples, the ratio of the ester solvent may be 3 parts by weight or more, 5 parts by weight or more, 7 parts by weight or more, 9 parts by weight or more, or 11 parts by weight or more, or 90 parts by weight or less, 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, 50 parts by weight or less, 40 parts by weight or less, 30 parts by weight or less, or 20 parts by weight or less.

[0084] The slurry may further include a binder. The type of such a binder is not particularly limited and can be appropriately selected depending on the type of metal component, solvent, or dispersant used during the production of the slurry. For example, the binder may be, but is not limited to, alkyl cellulose having an alkyl group with 1 to 8 carbon atoms, such as methyl cellulose or ethyl cellulose, polyalkylene carbonate having an alkylene unit with 1 to 8 carbon atoms, such as polypropylene carbonate or polyethylene carbonate, or polyvinyl alcohol-based binders such as polyvinyl alcohol or polyvinyl acetate (hereinafter, also referred to as polyvinyl alcohol compounds).

[0085] The ratio of each component in the slurry is not particularly limited, and may be adjusted in consideration of process efficiency, such as coatability and moldability, during a process using the slurry.

[0086] For example, in order to more effectively secure the desired porosity and surface roughness, the binder may be contained in the slurry at a ratio of about 1 to 500 parts by weight relative to 100 parts by weight of the metal component. In other examples, the ratio may be about 2 parts by weight or more, about 3 parts by weight or more, about 4 parts by weight or more, about 5 parts by weight or more, about 6 parts by weight or more, about 7 parts by weight or more, about 8 parts by weight or more, about 9 parts by weight or more, about 10 parts by weight or more, about 20 parts by weight or more, about 30 parts by weight or more, about 40 parts by weight or more, about 50 parts by weight or more, about 60 parts by weight or more, about 70 parts by weight or more, about 80 parts by weight or more, about 90 parts by weight or more, about 100 parts by weight or more, about 110 parts by weight or more, about 120 parts by weight or more, about 130 parts by weight or more, It may be about 140 parts by weight or more, about 150 parts by weight or more, about 200 parts by weight or more, or about 250 parts by weight or more, and may be about 450 parts by weight or less, about 400 parts by weight or less, about 350 parts by weight or less, about 300 parts by weight or less, about 250 parts by weight or less, about 200 parts by weight or less, about 150 parts by weight or less, about 100 parts by weight or less, about 50 parts by weight or less, about 40 parts by weight or less, about 30 parts by weight or less, about 20 parts by weight or less, about 10 parts by weight or less, about 8 parts by weight or less, or about 6 parts by weight or less.

[0087] In the slurry, the dispersant or solvent may be included in a ratio of about 0.5 to 2,000 parts by weight relative to 100 parts by weight of the binder in order to more effectively secure the desired porosity characteristics, etc. In other examples, the ratio may be about 1 part by weight or more, about 1.5 parts by weight or more, about 5 parts by weight or more, about 10 parts by weight or more, about 15 parts by weight or more, about 20 parts by weight or more, about 30 parts by weight or more, about 40 parts by weight or more, about 50 parts by weight or more, about 60 parts by weight or more, about 70 parts by weight or more, about 80 parts by weight or more, about 90 parts by weight or more, about 100 parts by weight or more, about 200 parts by weight or more, about 300 parts by weight or more, about 400 parts by weight or more, about 500 parts by weight or more, about 550 parts by weight or more, about 600 parts by weight or more, or about 650 parts by weight or more, and may be about 1,800 parts by weight or more. or less, about 1,600 parts by weight or less, about 1,400 parts by weight or less, about 1,200 parts by weight or less, or about 1,000 parts by weight or less, 900 parts by weight or less, about 800 parts by weight or less, about 700 parts by weight or less, about 600 parts by weight or less, about 500 parts by weight or less, about 400 parts by weight or less, about 300 parts by weight or less, about 200 parts by weight or less, about 150 parts by weight or less, about 130 parts by weight or less, about 110 parts by weight or less, about 100 parts by weight or less, about 50 parts by weight or less, about 30 parts by weight or less, about 20 parts by weight or less, about 10 parts by weight or less, or about 5 parts by weight or less.

[0088] In this specification, the unit parts by weight refers to the weight ratio between each component, unless otherwise specified.

[0089] The slurry may contain other necessary known additives in addition to the above-mentioned components. However, in order to effectively obtain the desired pore characteristics, surface roughness, etc., the slurry may not contain a so-called foaming agent. The term "foaming agent" includes not only components that are generally called foaming agents in the industry, but also components that can exhibit a foaming effect in relation to other components in the slurry. Therefore, in the process of producing the metal foam in this application, a foaming process may not be performed.

[0090] The types of additional components that may be included in the slurry are various, but a representative example is polymer beads that are pore-forming agents. Such polymer beads are present in the slurry and are removed during a sintering process, etc., to form pores in the areas where they were present in the slurry. The types of applicable polymer beads are not particularly limited, and beads that can be removed during the sintering process (e.g., polymer beads whose melting point is below the sintering temperature) and have an average particle size that matches the desired pore size can be used.

[0091] The slurry may also contain further additives which are known to be capable of acting as so-called levelling agents.

[0092] The method of forming the metal foam precursor using the slurry is not particularly limited. In the field of metal foam manufacturing, various methods for forming a metal foam precursor are known, and all of these methods can be applied to the present application. For example, the metal foam precursor can be formed by holding the slurry on a suitable template or coating the slurry in a suitable manner.

[0093] When manufacturing a metal foam in the form of a film or sheet according to one embodiment of the present application, it is advantageous to apply a coating process. For example, the slurry is coated on a suitable substrate to form a precursor, and then the desired metal foam can be formed through a sintering process described below. In this process, the surface roughness of the metal foam can be controlled by controlling the smoothness of the substrate surface on which the slurry is coated.

[0094] The form of the metal foam precursor is determined by the intended metal foam and is not particularly limited. In one example, the metal foam precursor may be in the form of a film, sheet or layer, such as in the case of a porous metal sheet.

[0095] In the process of forming the metal foam precursor, a suitable drying process may be performed. For example, the metal foam precursor may be formed by forming the slurry by the above-mentioned coating method and then drying for a certain period of time. The drying conditions are not particularly limited, and may be controlled, for example, at a level where the solvent contained in the slurry is removed to a desired level. For example, the drying may be performed by maintaining the formed slurry at a temperature within a range of about 50°C to 250°C, about 70°C to 180°C, or about 90°C to 150°C for an appropriate period of time. The drying time may also be selected within an appropriate range.

[0096] The metal foam precursor formed in the above manner may be sintered to produce the metal foam. In this case, the method of sintering to produce the metal foam is not particularly limited, and any known sintering method may be used. That is, the sintering may be performed by applying an appropriate amount of heat to the metal foam precursor in an appropriate manner.

[0097] In this case, the sintering conditions can be controlled in consideration of the state of the applied metal foam precursor, for example, the composition of the slurry or the type of metal powder, so that the metal powder is connected to form a porous structure, and the specific conditions are not particularly limited.

[0098] For example, the sintering can be performed by maintaining the precursor at a temperature in the range of about 500° C. to 2000° C., 700° C. to 1500° C., or 800° C. to 1200° C., and the maintenance time can also be selected arbitrarily. In one example, the maintenance time may be in the range of about 1 minute to 10 hours, but is not limited thereto.

[0099] If necessary, after forming the metal foam in the above manner, a metal layer formation process such as electrolytic plating or electroless plating may be carried out to form a porous metal sheet containing the first and second metals.

[0100] In order to secure the required impact resistance and realize the electromagnetic wave shielding ability and heat dissipation characteristics, the porosity of the metal foam can be controlled. For example, the porosity of the metal foam can be in the range of 50% to 80%. In other examples, the porosity of the metal foam can be 52% or more, 54% or more, 56% or more, 58% or more, 60% or more, 62% or more, 64% or more, 66% or more, or 68% or more, or 78% or less, 76% or less, 74% or less, or 72% or less. The porosity of such a metal foam can be calculated by a known method of converting the porosity through the volume, mass, density, etc. of the metal foam.

[0101] In another embodiment, the porous metal sheet may be a metal fiber sintered sheet or a metal mesh layer.

[0102] The term "sintered metal fiber sheet" refers to a sheet-like material produced by forming metal fibers into a sheet or film shape by applying a papermaking method or the like and fusing them through sintering, and the term "metal mesh" refers to a sheet-like material produced by braiding or weaving metal fibers into a mesh, wire net, web or woven fabric.

[0103] The above-mentioned sintered metal fiber sheet and / or metal mesh layer can provide a porous metal sheet having the desired electromagnetic wave shielding properties, heat dissipation properties, and shock absorption properties by controlling the applied material, thickness, and / or pores.

[0104] In order to ensure the required electromagnetic wave shielding properties, impact resistance and / or heat dissipation properties, the wire diameter, porosity and / or mesh properties of the metal fibers constituting the sintered metal fiber sheet and / or metal mesh layer can be controlled.

[0105] The wire diameter of the metal fiber means the diameter of the cross section of the metal fiber, and this wire diameter may be the wire diameter of the metal fiber in a state in which the sintered metal fiber sheet or metal mesh is formed, or the wire diameter of the metal fiber used as a raw material before being manufactured into the sintered metal fiber sheet or metal mesh.

[0106] For example, the metal fibers forming the sintered metal fiber sheet or the metal fibers used as a raw material for producing said sintered metal fiber sheet may have a fiber diameter in the range of 1 to 80 μm.

[0107] In one embodiment, the porosity of the sintered metal fiber sheet may be in the range of 40 to 80%. The porosity of the sintered metal fiber sheet may be calculated by a known method of converting the porosity into the volume, mass, density, etc. of the sintered metal fiber sheet.

[0108] For example, the metal fibers forming the metal mesh layer or the metal fibers used as a raw material for producing the metal mesh layer may have a wire diameter in the range of 25 to 100 μm.

[0109] The metal mesh layer may have a mesh size in the range of 100 to 200 mesh.

[0110] The sintered metal fiber sheet and / or metal mesh layer as described above may be constructed using known metal materials (metal fibers) without any particular restrictions. That is, the sintered metal fiber sheet and / or metal mesh layer can be constructed by selecting an appropriate material in consideration of the Young's modulus, resistivity, thermal conductivity, Poisson's ratio and / or density of the metals described above.

[0111] Various sintered metal fiber sheets and / or metal mesh layers are known, and various methods for manufacturing the sintered metal fiber sheets and / or metal mesh layers are also known. In the present application, such known sintered metal fiber sheets and / or metal mesh layers or metal fiber sheets and / or metal mesh layers manufactured by the known methods can be applied.

[0112] If necessary, the sintered metal fiber sheet and / or metal mesh layer may be subjected to a metal layer forming process such as electrolytic plating or electroless plating to include the desired first and second metals.

[0113] The porous metal sheet of the buffer film may include only one of the metal foam, the sintered metal fiber sheet, and the metal mesh layer, or may be a laminate or combination of two or more selected from the above.

[0114] The buffer film or the porous metal sheet contained therein may be substantially free of organic components such as polymers. This is important from the viewpoint of ensuring the desired heat dissipation characteristics and impact resistance. For example, a composite material in which a metal foam is combined with an organic component such as a polymer is known, but such a composite increases the thermal conductivity in the thickness direction of the metal foam and reduces the impact resistance. Therefore, in the present application, the buffer film or the porous metal sheet contained therein must be substantially free of the organic components. The above phrase "substantially free of organic components" means that the ratio of organic components in the buffer film or the porous metal sheet is about 5% by weight or less, 4.5% by weight or less, 4% by weight or less, 3.5% by weight or less, 3% by weight or less, 2.5% by weight or less, 2% by weight or less, 1.5% by weight or less, 1% by weight or less, or 0.5% by weight or less. Here, the ratio of the organic components does not include organic components contained in a layer applied to attach the porous metal sheet to a substrate, such as an attachment layer described later. There is no lower limit for the proportion of the organic component, and since it is necessary that no organic component is contained, the lower limit for the proportion may be 0% by weight.

[0115] The buffer film may further include an attachment layer for attaching the porous metal sheet to a substrate or the like. The attachment layer may be formed on one or both sides of the porous metal sheet. As described above, when the porous metal sheet includes first and second main surfaces having different surface roughnesses, the attachment layer may be formed on the main surface having the larger surface roughness. That is, as described above, when the first and second main surfaces of the porous metal sheet have different surface roughnesses and the first main surface has a larger surface roughness than the second main surface, the attachment layer may be formed on at least the first main surface.

[0116] As the attachment layer, there is no particular limitation, and a known adhesive layer or bonding layer can be used, and there is no particular limitation on the thickness thereof.

[0117] The buffer film may include other layers as required, for example a graphite sheet or layer may be present to improve the heat diffusion properties in the plane.

[0118] However, from the viewpoint of constructing a device as thin as possible, the buffer film may include only the porous metal sheet and the adhesive layer as components, thereby making it possible to construct an even thinner device. This is possible because the porous metal sheet included in the buffer film alone can ensure the electromagnetic wave shielding properties, heat dissipation properties, and impact resistance required for OLEDs, etc.

[0119] Therefore, the present application can provide a device such as an OLED that has the required heat dissipation, electromagnetic shielding, and impact resistance (or impact mitigation) with a simple structure without problems such as increased cost, complicated processes, and increased thickness.

[0120] The present application also relates to an OLED, in particular an OLED comprising said buffer film.

[0121] The OLED of the present application may include a substrate, an organic light-emitting layer formed on the substrate, and a buffer film formed on the substrate. Figure 2 is a schematic diagram showing an OLED including an organic light-emitting layer 20, a substrate 10, and a buffer film 100 in that order. The buffer film may be the same as the buffer film described above.

[0122] The terms "upper and lower" used above are terms used to define the positional relationship between the organic light emitting layer and the substrate such as the buffer film, etc. Therefore, the organic light emitting layer does not necessarily have to be located above the buffer film in actual transportation or use.

[0123] The type of the substrate applied to the OLED is not particularly limited. In general, when an OLED is constructed, a glass substrate or a plastic substrate is applied as the substrate, and in the present application, any commonly used substrate can be applied without limitation.

[0124] In one example, the substrate can be a plastic substrate. When a plastic substrate is used, it is advantageous for forming an OLED that is relatively thin and flexible. However, when a plastic substrate is used, the OLED becomes more vulnerable to external impacts and is difficult to effectively handle electromagnetic waves and heat. However, when the buffer film of the present application is applied, the above-mentioned disadvantages of the plastic substrate can be eliminated and its advantages can be obtained.

[0125] There is no particular limitation on the type of organic light-emitting layer formed on the substrate. In general, an organic light-emitting layer is present between an anode and a cathode facing each other and includes at least an organic layer including a light-emitting layer, and such a general configuration can be used in the present application without any particular limitation.

[0126] The organic layer may further include necessary known layers such as an electron injection layer, an electron transport layer, a hole transport layer and / or a hole injection layer in addition to the light emitting layer.

[0127] In the organic light-emitting layer, one of the positive electrode and the negative electrode may be a transparent electrode, and the other may be a reflective electrode, or in some cases, both electrodes may be transparent electrodes.

[0128] Methods and materials for forming an organic light-emitting layer through the above-mentioned configuration are well known, and such well-known methods and materials can be applied to the present application.

[0129] In the above structure, the buffer film is formed under the substrate and is a layer that can efficiently remove heat generated in the organic light emitting layer or other components of the OLED, block electromagnetic waves generated in the organic light emitting layer or approaching the organic light emitting layer, and reduce or eliminate external impacts.

[0130] Furthermore, as described above, when the buffer film has a porous metal sheet having different surface roughnesses on the first and second major surfaces and the first surface has a larger surface roughness than the second surface, the first major surface of the porous metal sheet in the buffer film may be positioned closer to the organic light-emitting layer than the second major surface.

[0131] In addition, by exhibiting the above-mentioned reflectivity, problems such as reduced visibility in OLEDs, etc. are not caused, and by ensuring the above-mentioned resistivity, conductive or insulating parts can be formed as needed in OLEDs, etc.

[0132] The OLED may further include an electronic element formed under the buffer film as an additional configuration, as shown in FIG. 3, which illustrates such a configuration, in which an organic light-emitting layer 20, a substrate 10, the buffer film 100, and an electronic element 40 are sequentially included.

[0133] The electronic element is configured to apply a signal to a driving circuit unit that drives the organic light-emitting layer. Thus, in the above case, the substrate or the organic light-emitting layer may include a driving circuit unit for driving the organic light-emitting layer, and the driving circuit unit may be connected to the electronic element.

[0134] 3, the buffer film 100 can block the mutual transfer of heat generated in the organic light emitting layer 20 and / or the electronic element 40, and can block the mutual propagation of electromagnetic waves generated in the organic light emitting layer 20 and / or the electronic element 40. In addition, even if components such as the substrate 10 are thin, the device can be prevented from being damaged by external impact.

[0135] The specific configurations of the electronic elements and the drive circuit section are not particularly limited, and known configurations can be applied.

[0136] In addition, in the above-mentioned configuration, only the buffer film may be present between the electronic element and the substrate, thereby making it possible to form a thinner device. This is possible because the porous metal sheet included in the buffer film alone can ensure the electromagnetic wave shielding properties, heat dissipation properties, and impact resistance required for OLEDs. Effect of the Invention

[0137] The present application provides a buffer film and uses thereof, and in particular can provide a buffer film for an organic light-emitting device and uses thereof. [Brief description of the drawings]

[0138] [Figure 1] FIG. 1 is a diagram illustrating the structure of a conventional OLED. [Diagram 2] 2 and 3 are exemplary diagrams showing the OLED of the present application. [Diagram 3] 2 and 3 are exemplary diagrams showing the OLED of the present application. [Figure 4] FIG. 4 is a set of photographs showing the process of evaluating impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0139] The present application will now be described in detail with reference to examples, but the scope of the present application is not limited to the following examples.

[0140] 1. Evaluation of reflectance of porous metal sheet The reflectance of the porous metal sheet (metal foam) included in the buffer film was evaluated for wavelengths of 400 to 800 nm using UV spectroscopy equipment (Shimadzu UV-2600, manufactured by Shimadzu). An integrating sphere (ISR-2600) was attached to the equipment, and the reflectance was measured manually in diffuse reflectance mode (diffuse reflectance measurement), with BaSO4 used as the standard material. Using this method, the reflectance was evaluated at intervals of 0.5 nm from 400 nm to 800 nm, and the evaluated reflectances were averaged to determine the reflectance.

[0141] 2.Evaluation of thermal diffusivity The thermal diffusivity of the porous metal sheet (metal foam) included in the buffer film was evaluated by LFA (Laser Flash Analysis), where the evaluated thermal diffusivity was the thermal diffusivity in the xy plane. The thermal diffusivity was measured using a microflash (LFA 46 Hyper flash, Netzsch) device (in-plane measurement mode). The thermal diffusivity was measured by punching a test piece (metal foam) into a circle with a diameter of about 25.4 mm.

[0142] 3.Evaluation of surface roughness The surface roughness of the porous metal sheet was measured using a 3D laser microscope (Keyence VK-X160 model).

[0143] 4.Evaluation of resistivity The resistivity of the porous metal sheet (metal foam) included in the buffer film was measured using the Four Point Probe (FPP) method, using a CMT-SR2000N (manufactured by AIT) as the equipment.

[0144] 5. Evaluation of impact resistance (impact attenuation) Impact resistance was evaluated using a ball drop device as shown in Figure 4. In Figure 4, reference numeral 1000 denotes the ball drop position, reference numeral 2000 denotes the sample position, and reference numeral 3000 denotes the measurement unit. A porous metal sheet (metal foam) was placed at the sample position in Figure 4, and balls of the same weight were dropped onto the porous metal sheet from the same height using a ball drop device, and the peak impact force was measured using the measurement unit. The table below shows the reduction rate of the peak impact force measured by dropping a ball without a porous metal sheet, compared to the results measured using the above method.

[0145] Example 1. A metal foam was produced as a porous metal sheet. The metal foam was produced using copper powder with an average particle size (median particle size, D50 particle size) of about 60 μm. The copper has a thermal conductivity of about 401 W / mK, a Young's modulus of about 110 to 128 GPa, a Poisson's ratio of about 0.34, and a resistivity of about 1.7 × 10 -6 Ωcm and density is 8.96g / cm 3 It is a material with a roughness of about 100 nm. A slurry was prepared by mixing 30 g of the copper powder, 20 g of terpineol, 8 g of ethylhexyl caprate, 3 g of polyvinyl acetate, and 1 g of a leveling agent (BYK, BYK-358N). The slurry was coated in the form of a film, dried in an oven at 120°C for 30 minutes, and then sintered at a temperature of about 1,000°C in a hydrogen / argon atmosphere for about 2 hours to prepare a metal foam. In this process, the slurry was coated on a smooth surface with almost no surface roughness, and the surface opposite to the surface coated on the smooth surface was exposed to air during sintering.

[0146] The copper metal foam thus formed was then plated with nickel, which has a thermal conductivity of about 91 W / mK, a Young's modulus of about 200 GPa, a Poisson's ratio of about 0.31, and a resistivity of about 6.9×10-6 Ωcm and density is 8.908g / cm 3 It is a material that is about the same quality as the original.

[0147] The electrolytic plating was performed in a known manner. That is, the copper metal foam was placed in a solution containing NiSO4, NiCl2, or H2BO3, and the surface of the copper metal foam was plated with nickel by electrolytic plating in which a platinum electrode and the copper metal foam were applied to the positive and negative electrodes, respectively. The plating was continued for about 1 minute to obtain a nickel-plated copper metal foam. The nickel plating thickness on the copper metal foam was about 97 nm. The nickel plating thickness was confirmed by observing a sample (metal foam) with a scanning electron microscope (SEM) in a state in which the cross section was exposed by cutting the sample (metal foam) with a focused ion beam (FIB). The manufactured metal foam had a thickness of about 150 μm and a porosity of about 74%. In addition, the surface roughness 1Sa of one surface (first main surface) of both sides of the metal foam was about 8.2 μm, and the surface roughness 2Sa of the other surface (second main surface) was about 5.5 μm. An acrylic adhesive layer was formed on the first main surface to prepare a buffer film.

[0148] Example 2. A porous metal sheet was manufactured in the same manner as in Example 1, but nickel plating was performed for 2 minutes to manufacture a porous metal sheet. The nickel plating thickness on the copper metal foam was about 142 nm. The metal foam manufactured as described above had a thickness of about 151 μm and a porosity of about 74%. In addition, the surface roughness 1Sa of one surface (first main surface) of both sides of the metal foam was about 8.2 μm, and the surface roughness 2Sa of the other surface (second main surface) was about 5.5 μm. An acrylic adhesive layer was formed on the first main surface to manufacture a buffer film.

[0149] Example 3. A porous metal sheet was manufactured in the same manner as in Example 1, but nickel plating was performed for 4 minutes to manufacture a porous metal sheet. The nickel plating thickness on the copper metal foam was about 209 nm. The metal foam manufactured as described above had a thickness of about 153 μm and a porosity of about 72%. In addition, the surface roughness 1Sa of one surface (first main surface) of both sides of the metal foam was about 8.1 μm, and the surface roughness 2Sa of the other surface (second main surface) was about 5.5 μm. An acrylic adhesive layer was formed on the first main surface to manufacture a buffer film.

[0150] Example 4. A porous metal sheet was manufactured in the same manner as in Example 1, but nickel plating was performed for 8 minutes to manufacture a porous metal sheet. The nickel plating thickness on the copper metal foam was about 536 nm. The metal foam manufactured as described above had a thickness of about 155 μm and a porosity of about 70%. In addition, the surface roughness 1Sa of one surface (first main surface) of both sides of the metal foam was about 8.0 μm, and the surface roughness 2Sa of the other surface (second main surface) was about 5.5 μm. An acrylic adhesive layer was formed on the first main surface to manufacture a buffer film.

[0151] Example 5. An acrylic adhesive layer was formed on the second main surface of the porous metal sheet prepared in Example 1 to prepare a buffer film.

[0152] Comparative Example 1 A buffer film was prepared by forming an adhesive layer on a first major surface of the same copper metal foam prepared in Example 1 without further nickel plating.

[0153] The evaluation results for each of the Examples and Comparative Examples are shown in Table 1.

[0154] In Table 1 below, the electromagnetic wave shielding ability is the result of measurement in the range of 30 MHz to 1.5 GHz according to the ASTM D4935 standard.

[0155] [Table 1]

[0156] From Table 1, it can be seen that the buffer film according to this embodiment can independently satisfy the impact resistance, heat dissipation property, and electromagnetic wave shielding property required for OLEDs, etc.

[0157] In addition, it can be seen that the porous metal sheet of the buffer film of the Example exhibits low reflectance and does not cause visibility problems when included in an OLED, and exhibits appropriate resistivity to form insulating or conductive parts required in an OLED, etc. On the other hand, it can be seen that the buffer film of Comparative Example 1 exhibits excessively high reflectance. [Explanation of symbols]

[0158] 10 Substrate 20 Organic light-emitting layer 30, 40 Electronic elements 100 Buffer Film

Claims

1. The porous metal sheet has an average reflectance of 50% or less for light in the wavelength range of 400 to 800 nm; The porous metal sheet includes a first metal and a second metal different from the first metal; the first metal is copper and the second metal is nickel; the porous metal sheet is formed by electrically or chemically coating the second metal on a surface of the first metal; The first and second main surfaces of the porous metal sheet have different surface roughnesses, and the ratio 1Sa / 2Sa of the surface roughness 1Sa of the first main surface to the surface roughness 2Sa of the second main surface is greater than 1 and less than or equal to 3; The surface roughness of the buffer film is an index (Sa) representing the arithmetic mean height.

2. The porous metal sheet has a resistivity of 1.0 x 10 -5 2. The buffer film according to claim 1, having a resistivity of Ωcm or more and 9×10 −5 Ωcm or less.

3. The porous metal sheet has a thermal diffusion coefficient of 25 mm. 2 The buffer film according to claim 1 or 2, having a linear modulus of not less than 300 mm 2 / s and not more than 300 mm 2 / s.

4. The buffer film according to claim 1 , wherein the surface roughness 1Sa of the first main surface is 6.5 μm or more and 20 μm or less.

5. The buffer film according to any one of claims 1 to 4, wherein the thickness of the porous metal sheet is 50 µm or more and 1000 µm or less.

6. The porous metal sheet includes a first metal having a Young's modulus of 50 GPa or more and 160 GPa or less, and a second metal having a Young's modulus of more than 160 GPa and 400 GPa or less. The buffer film according to any one of claims 1 to 5.

7. The porous metal sheet has a resistivity of 0.5×10 −6 Ωcm or more and 4.3×10 -6 A first metal having a resistivity of 4.3×10 -6 and a second metal having a resistivity of more than 15×10 −6 Ωcm or less.

8. The buffer film according to any one of claims 1 to 7, wherein the first and second metals each have a Poisson's ratio within the range of 0.1 to 0.

7.

9. The buffer film according to any one of claims 1 to 8, wherein the porous metal sheet is a metal foam, a sintered metal fiber sheet or a metal mesh.

10. The buffer film of any one of claims 1 to 9, further comprising an attachment layer present on one or both sides of the porous metal sheet.

11. The buffer film according to claim 10 , wherein an attachment layer is formed on at least the first main surface.

12. A substrate; an organic light-emitting layer formed on the substrate; and the buffer film according to any one of claims 1 to 11 formed under the substrate.

13. 13. An organic light emissive device according to claim 12, wherein the first major surface is disposed closer to the organic light emissive layer than the second major surface.

14. The organic light-emitting device according to claim 12 or 13, further comprising an electronic element formed below the buffer film, wherein only the buffer film is present between the electronic element and the substrate.

Citation Information

Patent Citations

  • Organic electroluminescent display with porous material layer

    CN1592516A

  • El lamp with noise preventing structure

    JP2000252057A

  • Display apparatus and plasma display apparatus

    JP2005107487A

  • Reflective substrate

    JP2006243199A

  • Porous metal thin film and manufacturing method thereof as well as capacitor

    JP2009164412A